High variation between healthcare professionals in nutrition therapy plans of patients with feeding tubes admitted to a long‐term rehabilitation center from an acute‐care hospital. (25th September 2022) - Marom, Pnina; Rayyan‐Assi, Hana'a; Stein‐Reisner, Orit; Brik, Michael; Gershoni‐Kait, Michal; Bornstein, Lee; Zalcman, Beth G.; Albukrek, Dov; Dankner, Rachel
Abstract: Background: Nutrition therapy plans (NTPs) in discharge summaries of tube‐fed patients transferred from acute‐care hospitals to rehabilitation centers are fundamental for continuity of care. This study examined the presence and quality of NTPs in discharge summaries of tube‐fed patients. Methods: This cross‐sectional study was based on data retrieved from electronic medical records. The outcome measures were the presence of NTPs in discharge summaries, the presence of key elements of the NTPs, and the level of compatibility between multiple NTPs per discharge summary prepared by different health professionals. Descriptive statistics were used to assess the number of NTPs, the presence of key elements, and the degree of compatibility between NTPs for the same patient. Results: A total of 100 discharge summaries of tube‐fed patients admitted to a rehabilitation hospital during 2015–2017 were identified. The majority (91%) of discharge summaries included at least one NTP; 57 included more than one. Variance in the presence of key elements was observed in 165 NTPs prepared by physicians, nurses, and dietitians. Water amount and nutrition route were least reported by dietitians (6.3% and 9.4%, respectively), compared with physicians (77.6% and 81%) and nurses (77.3% and 62.7%). However, nutrition details were reported more frequently by dietitians (65.6%) than physicians (20.7%) and nurses (32%). Low compatibility was observed between dietitians and both nurses and physicians, in the range of 0%–26%. Conclusion: Large discrepancies were found between NTPs for the same patient prepared by dietitians, physicians, and/or nurses, and a portion of patients arrived without any NTP.